IOT‑Based Smart Crop Cultivation & Monitoring - Khan, Ateeb Ali; Khan, Emran Ullah; Bilal, Muhammad; Majid, Saad Ijaz (Digital Technologies Research and Applications, 2025)
With the requirement for new and effective procedures to improve crop cultivation, blending of modern technology, such as the Internet of Things (IoT), and ancient agricultural methods holds greater relevance. In the following study, the feasibility and importance of implementing an IoT-based smart crop cultivation and monitoring system are discussed. The smart agricultural technology will provide control, anti-toxic, and an optimum level of environment to yield crops in any remote or short on resources areas across the globe and beyond. The smart agricultural system enables professionals to manage, monitor, and analyze crop yields remotely with the help of an integrated mobile application. With limitations in natural resources and time, crop cultivation needs to be robust but safe and technologically empowered through smart agricultural systems such as the one we are presenting. The research work aims to mitigate the carbon footprint associated with conventional agriculture, add more precision to the crop yield by offering an optimized farming space, educate the farmers about advanced technology, and most importantly, enable quality crop cultivation in remote regions. With the help of IoT, the proposed procedure for crop cultivation gets precision in results, scalability for resources, remote control, and an optimized environment for cultivating multiple crops.